2003
DOI: 10.1046/j.1526-4610.2003.03062_16.x
|View full text |Cite
|
Sign up to set email alerts
|

Patent foramen ovale, a possible cause of symptomatic migraine: a study of 74 patients with acute ischemic stroke.

Abstract: Cerebrovasc Dis. 2002;13(2):102‐106 Recent studies reported an increased prevalence of patent foramen ovale (PFO) in patients with migraine with aura (MA  +). To investigate the possible relationship between MA  + and paradoxical embolism, we studied the prevalence of both conditions. Investigation of PFO was undertaken in 74 consecutive patients presenting with an acute stroke of undetermined origin. The patients were questioned about MA  + or migraine without aura (MA  −) according to the criteria of the Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0
3

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 0 publications
4
75
0
3
Order By: Relevance
“…The passage of more than 3 microemboli in the following three cardiac cycles was considered a diagnosis for PFO. This procedure was repeated a maximum of four times [6].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The passage of more than 3 microemboli in the following three cardiac cycles was considered a diagnosis for PFO. This procedure was repeated a maximum of four times [6].…”
Section: Methodsmentioning
confidence: 99%
“…A high prevalence of MA is reported in patients with paradoxical embolism, suggesting a possible role of this association in the occurrence of cerebrovascular events [6]. Right-to-left shunts are also associated with some forms of decompression illness, suggesting the possibility that these shunts have a role in the aetiology of MA [7].…”
mentioning
confidence: 99%
“…In fact, an association between stroke, PFO and migraine has been reported [5,18,19]. Along with stroke, however, migraine and particularly MA have been the focus of greater interest in studies on PFO.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, some studies have reported an inc reased prevalence of PFO in patients with migraine with aura, and closure of PFO was associated with complete disappearance of migraine attacks in some patients 14,15 . Although this is not be the aim of this paper, in our small series, two patients (mother and daughter, 6 and 4 respectively) re p o rted disappearance of aura and reduction of migraine attacks along 28 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%